A Review on Planer Scissor Mechanisms for Spatial Deployable Structures - Jung, Teck (International Journal of Psychosocial Rehabilitation, 2020)
this paper reviewed planar scissor mechanisms (SMs) in the applications of spatial deployable structures. These SMs consists of two beams connected by revolute joint behaves as mechanism during deployment and load bearing structure at deployed configuration. By altering the scissor unit middle joint position or modify scissor elements, various geometry shapes can be formed and additional locking devices is needed for SMs stabilization in final configuration. There are numerous studies have been conducted by experimentally, numerically and analytically to understand the SMs behaviour for spatial deployable structure applications. Although there are many studies dealing with designing new planar SMs in the application of spatial deployable structure and their calculation methods based on researcher’s developed profiles, this topic still been an open topic to be carried out based on their geometric shapes and architectural functions. Therefore, this review aims to provide an overview of SMs behaviours in transforming the folded configuration structure element become spatial deployable structure. The reviewed papers covered the SMs problems, analysis methods and solutions in the application of spatial deployable structures. Based on the reviewed findings, stabilization is the main problem identified for the SMs. The simple geometry approach was used to analyse the system and various stabilization methods proposed subjected to the structures profiles and geometric principle. The deployability conditions and basic scissor unit types must be examined in term to understand their geometric design principles. On the basis of these SMs, the reviewed outcomes are herein will contribute to the better understanding of the SMs behaviours in spatial deployable structures application.